Comparison of Three Temperatures for the Hatching Phase in the Artificial Incubation of Red-legged Partridge (Alectoris rufa) Eggs - González-Redondo,P (2016)
ABSTRACT This study aimed at investigating the effects of three incubation temperatures during the hatching period on egg weight loss, hatchability, chick weight at hatching and length of the incubation period of red-legged partridge (Alectoris rufa) under artificial incubation. One hundred and fifty eggs obtained from a red-legged partridge game farm were randomly allocated to three batches of 50 eggs each. Eggs were incubated at 37.8ºC during the first 20 days, and subsequently at 37.0, 37.4 or 37.8ºC until hatching. Fertility was 74.7% and a good hatching performance was obtained, characterized by 85.7% hatchability, 9.1% egg weight loss after 20 days of incubation, 13.8±0.1 g chick weight at hatching, and 23.2±0.1 days incubation length. Hatchability, egg weight loss after 20 days of incubation, and length of the incubation period were not affected by incubation temperature during the hatching period. However, hatching synchrony improved when the incubation temperature was increased from 37.0 to 37.8°C (p<0.05). Thus, hatching distribution became very leptokurtic and very positively skewed with the increase in incubation temperature during the hatching phase. In conclusion, higher hatching synchrony can be achieved in A. rufa when setting temperatures within the range 37.0 to 37.8ºC to incubate eggs during the hatching period. Consequently, incubation temperature management during the hatching phase may have a direct impact on hatching synchrony and hatchling management.